Massive Open Online Courses for Health Worker Education in Low- and Middle-Income Countries: A Scoping Review - Nieder, Jessica; Nayna Schwerdtle, Patricia; Sauerborn, Rainer; Barteit, Sandra (Frontiers in Public Health, 2022)
Background: Massive Open Online Courses (MOOCs) have the potential to improve access to quality education for health care workers (HCWs) globally, and in low- and middle-income countries (LMICs). Although studies have reported on the use of MOOC in LMICs, there is limited insight on the barriers and facilitators to their access and utilisation. We conducted a scoping review to map published peer-reviewed literature on MOOCs for HCW education in LMICs. We systematically searched four academic databases (Scopus, Web of Science, PubMed, ERIC) and Google Scholar, and undertook a two-stage screening process. The analysis included studies that reported on a MOOC relevant to HCWs’ education that were accessed by HCWs based in LMICs. Results: The search identified 1317 studies of which 39 studies were included in the analysis, representing 40 MOOCs accessed in over 90 LMICs. We found that MOOCs covered a wide range of HCWs’ including nurses, midwives, physicians, dentists, psychologists, and other workers from the broader health care sector, mainly at a post-graduate level. Dominant topics covered by the MOOCs included infectious diseases and epidemic response, treatment and prevention of non-communicable diseases, communication techniques and patient interaction, as well as research practice. Time contribution and internet connection were recognised barriers to MOOC completion, whilst deadlines, email reminders, graphical design of the MOOC, and blended learning modes facilitated uptake and completion. MOOCs predominantly taught in English (20%), French (12.5%), Spanish (7.5%) and Portuguese (7.5%). Overall, evaluation outcomes were positive and focused on completion rate, learner gain, and student satisfaction. Conclusion: We conclude that MOOCs are an adequate tool to support HCWs’ education in LMICs and may be particularly suited for supporting knowledge and understanding. Heterogeneous reporting of MOOC characteristics limits our ability to evaluate MOOCs at a broader scale; we make suggestions of how standardized reporting may offset this problem. Further research should focus on the impact of learning by MOOC on the impacts on HCWs’ work as well as the apparent lack of courses covering the key causes of disease in LIMCs to better understand the extent to which MOOCs can be utilized in this context.